Early Neural Markers of Implicit Attitudes: N170 Modulated by Intergroup and Evaluative Contexts in IAT - Ibanez, Agustin; Gleichgerrcht, Ezequiel; Hurtado, Esteban; González, Ramiro; Haye, Andrés; Manes, Facundo F. (Frontiers in Human Neuroscience, 2010)
The Implicit Association Test (IAT) is the most popular measure to evaluate implicit attitudes. Nevertheless, its neural correlates are not yet fully understood. We examined event related potentials (ERPs) in response to face- and word- processing while indigenous and non-indigenous participants performed an IAT displaying faces (ingroup and outgroup members) and words (positive and negative valence) as targets of category judgments. The N170 component was modulated by valence of words and by ingroup/outgroup face categorization. Contextual effects (face-words implicitly associated in the task) had an influence on the N170 amplitude modulation. On the one hand, in face categorization, right N170 showed differences according to the association between social categories of faces and affective valence of words. On the other, in word categorization, left N170 presented a similar modulation when the task implied a negative valence associated with ingroup faces. Only indigenous participants showed a significant IAT effect and N170 differences. Our results demonstrate an early ERP blending of stimuli processing with both intergroup and evaluative contexts, suggesting an integration of contextual information related to intergroup attitudes during the early stages of word and face processing. To our knowledge, this is the first report of early ERPs during an ethnicity IAT, opening a new branch of exchange between social neuroscience and social psychology of attitudes.